2019
DOI: 10.1007/s13555-019-00319-0
|View full text |Cite
|
Sign up to set email alerts
|

Topical Non-Pharmacological Treatment for Facial Seborrheic Dermatitis

Abstract: Facial seborrheic dermatitis (FSD) is a chronic and relapsing inflammatory skin disorder occurring in areas of the face rich in sebaceous glands. It clinically manifests as erythematous scaly macules or plaques, often associated with pruritus. Although the pathogenesis of seborrheic dermatitis is not yet fully understood, Malassezia yeast, hormones, sebum levels, and immune response are known to play important roles. Additional factors including drugs, cold temperatures, and stress may e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
1
24
0
2
Order By: Relevance
“…The results revealed that one of the tested complexes demonstrated similar activity to ZnPCA [20,39], and other two demonstrate better antibacterial properties.…”
Section: Antibacterial Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…The results revealed that one of the tested complexes demonstrated similar activity to ZnPCA [20,39], and other two demonstrate better antibacterial properties.…”
Section: Antibacterial Activitymentioning
confidence: 97%
“…Zinc oxide, zinc gluconate, zinc pyrithione, and zinc 2-pirrolidone 5-carboxylate (ZnPCA) are also common ingredients in sunscreens and anti-acne and anti-dandruff agents [17][18][19][20]. However, to overcome drug resistance, new antimicrobial agents are always required for dermatological disorders, especially for acne vulgaris.…”
Section: Introductionmentioning
confidence: 99%
“…For mild to moderate facial and chest SD, topical drugs play a key role in the management by reducing erythema and scale production. A variety of treatments including topical corticosteroids, antifungal agents, calcineurin inhibitors and, more recently, non-steroidal creams, are available [14]. To date, it is available a novel nonsteroidal cream (NSC) containing different ingredients, which have been reported to exert effects in SD treatment [14].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of treatments including topical corticosteroids, antifungal agents, calcineurin inhibitors and, more recently, non-steroidal creams, are available [14]. To date, it is available a novel nonsteroidal cream (NSC) containing different ingredients, which have been reported to exert effects in SD treatment [14]. In particular, this cosmeceutical is composed of: (1) piroctone olamine, that has an anti-fungal property [15][16][17]; (2) zinc salt of L-pyrrolidone carboxylate (PCA), that has anti-fungal and anti-inflammatory properties [18][19][20];…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation